2020
DOI: 10.3390/molecules25173866
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Thin Coatings Containing Anthriscus sylvestris Extract with Dual Bioactivity

Abstract: Plant extracts are highly valuable pharmaceutical complexes recognized for their biological properties, including antibacterial, antifungal, antiviral, antioxidant, anticancer, and anti-inflammatory properties. However, their use is limited by their low water solubility and physicochemical stability. In order to overcome these limitations, we aimed to develop nanostructured carriers as delivery systems for plant extracts; in particular, we selected the extract of Anthriscus sylvestris (AN) on the basis of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…The antibacterial efficacy was evaluated against Staphylococcus aureus and Escherichia coli, while antifungal activity was evaluated toward Candida albicans. The results confirmed the antimicrobial effectiveness of the A. sylvestris extracts and demonstrated that the developed coating could facilitate sustained activity of this extract for at least 72 h [155].…”
Section: Antibacterial Activitysupporting
confidence: 70%
See 1 more Smart Citation
“…The antibacterial efficacy was evaluated against Staphylococcus aureus and Escherichia coli, while antifungal activity was evaluated toward Candida albicans. The results confirmed the antimicrobial effectiveness of the A. sylvestris extracts and demonstrated that the developed coating could facilitate sustained activity of this extract for at least 72 h [155].…”
Section: Antibacterial Activitysupporting
confidence: 70%
“…The reported antitumor efficacy of the A. sylvestris extract is preserved in these coatings, with the developed nanostructured thin films ensuring controlled release for at least 3 days. Hence, these coatings offer practical solutions for developing natural and bioactive materials with multifunctional applications [ 155 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…Authors in several studies have investigated the protective effect of natural products or their extracts against the side effects associated with IONPs including Echinacea purpurea [ 30 ] and Anthriscus sylvestris [ 31 ] extracts. In the current study, we investigated the protective role of quercetin against the toxicity of IONPs in the brains of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to fabricate a variety of biomaterials in the form of thin films, with reasonably uniform material spreading over relatively large regions, controlled film thickness, and good substrate adhesion is one of the many benefits of laser-based technologies [ 18 , 19 ]. Matrix-assisted pulsed laser evaporation (MAPLE) is a deposition laser-based technique which involves low material consumption and preserves the stoichiometry of the growing layers [ 8 , 20 ].…”
Section: Introductionmentioning
confidence: 99%